Analisis Peran Orang Tua dalam Proses Pembelajaran di Era Covid-19 pada Siswa Kelas II SDN Larangan 5 Kota Tangerang - Dewi, Nur Herni Hernawati; Nurfadhillah, Septy; Sa’odah, Sa’odah (Lembaga Yasin AlSys, 2022)
The purpose of this study was to find out how the role of parents in learning in the Covid-19 era in grade II students of SDN Larangan 5. The research method used in this study was qualitative research with descriptive type. The results of this study indicate that in the implementation of learning that is using the Whatsapp application. Learning is done through chat in Whatsapp groups and the provision of learning videos from youtube. Sometimes the teacher uses voice notes to explain the material, but this is rarely done. In addition, the role of parents as caregivers and educators as well as mentors for children has been carried out well. Parents also provide motivation so that their children can complete their assignments on time, and parents also facilitate cellphones, WiFi and internet quotas to support learning so that learning can run well. There are also advantages to online learning, including more flexible time, and learning can be done anywhere. However, online learning also has drawbacks, including an unstable internet network and many working parents so that the child's learning process becomes hampered.